LDA FACE RECOGNITION FOR SECURE VOTING SYSTEM - priyanka; jagadeesh (International Journal of Psychosocial Rehabilitation, 2020)
The Electronic Voting Machine (EVM) is utilized to record the vote cast by people in general rather than polling form papers utilized in conventional democratic frameworks. EVM is a basic gadget that is worked effectively by the surveying officials and the voters. A portion of the residents are not ready to be introduced on the day of the political decision because of some legitimate reasons or because of outstation. Another framework is being proposed right now to increment the level of casting a ballot called e-casting a ballot framework, which helps the individuals who are not ready to go to their particular surveying stall upon the arrival of a political decision because of legitimate reasons.